Pain management, fluid therapy and thromboprophylaxis after pancreatoduodenectomy: a worldwide survey among surgeons - Groen, Jesse V.; Henrar, Rutger B.; Hanna Sawires, Randa G.; AlEassa, Essa; Martini, Chris H.; Bonsing, Bert A.; Vahrmeijer, Alexander L.; Besselink, Marc G.; Pecorelli, Nicolo; Hackert, Thilo; Ishizawa, Takeaki; Miller, Timothy; et al. (HPB, 2022)
Background - The aim of this survey was to assess practices regarding pain management, fluid therapy and thromboprophylaxis in patients undergoing pancreatoduodenectomy on a global basis. - Methods - This survey study among surgeons from eight (inter)national scientific societies was performed according to the CHERRIES guideline. - Results - Overall, 236 surgeons completed the survey. ERAS protocols are used by 61% of surgeons and respectively 82%, 93%, 57% believed there is a relationship between pain management, fluid therapy, and thromboprophylaxis and clinical outcomes. Epidural analgesia (50%) was most popular followed by intravenous morphine (24%). A restrictive fluid therapy was used by 58% of surgeons. Chemical thromboprophylaxis was used by 88% of surgeons. Variations were observed between continents, most interesting being the choice for analgesic technique (transversus abdominis plane block was popular in North America), restrictive fluid therapy (little use in Asia and Oceania) and duration of chemical thromboprophylaxis (large variation). - Conclusion - The results of this international survey showed that only 61% of surgeons practice ERAS protocols. Although the majority of surgeons presume a relationship between pain management, fluid therapy and thromboprophylaxis and clinical outcomes, variations in practices were observed. Additional studies are needed to further optimize, standardize and implement ERAS protocols after pancreatic surgery.
Available online 24 September 2021
Gesehen am 29.06.2022